Optimalisasi Komposisi Media Dan Molase Pada Hasil Pleurotus Ostreatus - Nanik Lutfiyah; Dwi Indah Fitriani (Nucleus Journal, 2023)
This study investigated the optimal use of wood species and molasses in cultivating Pleurotus ostreatus, commonly known as oyster mushroom. Previous studies have often neglected the specific impact of different wood media on mushroom yield, leading to inconsistent results in productivity. This study addresses these shortcomings by systematically evaluating the effects of wood species, including sengon, kapok, and teak, and adding molasses as a nutrient source. The methodology involved controlled experiments to assess growth parameters, including the duration of mycelial spread and the total number of fruiting bodies produced. The novelty of this study lies in the comprehensive approach of combining wood species selection with nutrient supplementation, which has not been extensively explored in previous studies. The results showed that sengon wood significantly increased fruiting body yield compared to kapok and teak, with an average of 12 fruiting bodies per bunch. This study not only provides insights into effective mushroom cultivation practices but also highlights the potential for increased productivity through strategic media selection and nutrient addition. Future benefits of this study include improved agricultural practices for mushroom farmers, leading to higher yields and better economic returns. These findings can serve as a basis for further studies aimed at optimizing mushroom cultivation techniques, ultimately contributing to sustainable agricultural development.